Tinjauan Faktor Penyebab Pengembalian Klaim BPJS Pasien Rawat Inap di RSKD Duren Sawit Jakarta Timur Tahun 2021 - Alex Sander; Laela Indawati; Lily Widjaja; Nanda Aula Rumana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
BPJS claim returns have 2 types of returns, the first is a purification failure or a return that occurs due to incompatibility and incompleteness of patient administration, such as patient eligibility letter number (SEP), class of care, and way of returning the patient. The second is pending, this return occurs due to discrepancies and incomplete diagnoses, diagnosis codes and service files received by inpatient BPJS patients submitted to BPJS. Therefore, officers must have thoroughness and understanding when carrying out their duties. This study was conducted to determine the factors causing the return of BPJS claims for inpatients at the Duren Sawit Hospital, East Jakarta in 2021 using a descriptive quantitative approach, by providing an overview and results regarding the factors causing the return of BPJS claims for inpatients. The results of the study used 227 samples of claim files that were returned by the BPJS verifier and obtained 2 (two) types of claim returns. 54 (23.8%) failed to be purified and 173 (76.2%) pending claim files. The most reason for returning claims is that the diagnosis is not supported by treatment and supporting results. There are 2 factors hindering the identification of 5M. Man factor: human error, competence of officers, and the absence of a casemix team. Material: inaccuracy of diagnosis in electronic medical resume so that there is inaccuracy when coding patient diagnosis. There are no barriers to the Money, Method, Machine factors. To get maximum results when submitting BPJS claims for inpatients, hospitals should pay attention to the competence of officers and socialize policies that are in accordance with the system run by the hospital.